Mapping the path to good grades and positive well-being : the effects of passion, grit and achievement goals - Chan, Samuel Zhen Yu (2018)
Students experience great pressure in their pursuit of grades and often forsake their well-being in the process. Thus, there is a great need to identify factors which lead to both academic performance and positive well-being. This research aimed to identify how dimensions of passion, achievement goals and grit were interrelated and how they jointly contributed to both outcomes of academic performance and positive well-being. 175 undergraduate students were administered a survey measuring these constructs. Results from structural equation modelling revealed that academic performance was found to be predicted by harmonious passion, performance-approach goals and perseverance of effort (grit). Dimensions of positive well-being were positively predicted by harmonious passion, mastery-approach goals and perseverance of effort. They were also negatively predicted by obsessive passion. Perseverance of effort was predicted by mastery-approach goals and performance-approach goals while mastery-approach goals were predicted by harmonious passion. Furthermore, mastery-approach goals were found to mediate the effect between harmonious passion and perseverance of effort. Recommendations based on the models that contribute to both academic performance and positive well-being are discussed.